(untitled) (International Research in Economics and Finance, 2020)
This study aims to determine the effect of regional government characteristics on the financial performance of district / city regional governments in West Kalimantan. This research uses multiple regression. The dependent variable used is the regional financial performance which is proxied from the level of efficiency while the independent variables used are total assets, regional expenditure, DAU, PAD, and leverage as indicators of local government characteristics. The findings of this study indicate that regional spending and dependency of district / city regional governments in West Kalimantan on central government have an influence on the financial performance of district / city governments in West Kalimantan, while government size, prosperity and leverage have no influence on the financial performance of district governments / city in West Kalimantan.